Isolation, characterization and control of Botrytis spp. pathogenic on strawberry in Iran - Fatemeh Maghsoodi; Parissa Taheri; Saeed Tarighi (Heliyon)
This study was performed to identify Botrytis species pathogenic on strawberry and investigate effect of Ferula gummosa essential oil (EO) against Botrytis spp. The infected plant samples were collected in Khorasan Razavi province from strawberry fruits with gray mold disease symptoms. Following purification of the fungi, of the 54 isolates, 53 isolates were identified as B. cinerea and 1 isolate belonged to B. pelargonii based on morphological and molecular (ITS and RPB2 sequences) identification. The EO obtained from F. gummosa at 125, 250, 500, 750 and 1000 μg mL−1 concentrations showed significant antifungal effect on mycelial growth of B. cinerea and B. pelargonii in a dose dependent manner. Also, the EO at all concentrations tested strongly inhibited spore germination of B. cinerea and B. pelargonii. Treatment with the EO at EC50 concentration significantly reduced the sclerotia production of B. cinerea and B. pelargonii. Light and electron microscopy observations showed that F. gummosa EO at EC50 concentration caused morphological changes in the fungal structures. This EO reduced the activity of cell wall degrading enzymes, such as cellulase and pectinase produced by both fungal species. A total of 22 compounds were identified in the EO by gas chromatography-mass spectrometry. The major compounds of F. gummosa EO were β-Pinene (% 37.7), γ-Terpinene (% 21) and a-pinene (% 12). Moreover, the F. gummosa EO at 500, 750 and 1000 μg mL−1 concentrations considerably reduced the disease severity and infection of strawberry fruits by B. cinerea and B. pelargonii. According to the results of this study, inhibitory effect of F. gummosa EO was impressive in controlling strawberry postharvest gray mold disease. This is the first report on inhibitory ability of F. gummosa EO against strawberry postharvest gray mold disease, which can be suggested as a preserver coating for the fruits to extend their shelf life during storage period.